Moxibustion treatment increases the survival rate of lung infection of patients bed-ridden due to osteoporotic fracture of the spine via regulation of the inflammatory responses - Yaonan Cheng; Qin Chen; Ru Huang; Chunbo Lao; Wenbin Fu (Archives of Medical Science, 2023)
Introduction This study aimed to investigate the potential role of moxibustion (MOX) in the treatment of lung infection in patients bed-ridden due to osteoporotic fracture of the spine.